312 Risk Factors and Clinical Outcomes of Dysphagia After Anterior Cervical Surgery in Patients With Degenerative Cervical Myelopathy: Results From the AOSpine International and North America Studies. (August 2016) - Tetreault, Lindsay; Nagoshi, Narihito; Nakashima, Hiroaki; Arnold, Paul M.; Barbagallo, Giuseppe; Kopjar, Branko; Fehlings, Michael G.
Abstract : INTRODUCTION: The objective of this study is to determine the incidence and risk factors of postoperative dysphagia and to evaluate short- and long-term clinical outcomes in patients with this complication. METHODS: Four hundred seventy patients undergoing an anterior or a 2-stage surgery were enrolled in the prospective AOSpine CSM-North America or International study at 26 global sites. Logistic regression analyses were conducted to determine important clinical and surgical predictors of dysphagia. Preoperatively and at each follow-up, patients were evaluated using the modified Japanese Orthopedic Association scale (mJOA), Nurick score, Neck Disability Index (NDI), and the SF-36. A mixed model analytic approach was used to evaluate differences in outcomes at 6 and 24 months between patients with and without dysphagia, while controlling for relevant baseline characteristics and surgical factors. RESULTS: The overall incidence of dysphagia was 6.17%. Univariately, the major risk factors for perioperative dysphagia were a higher comorbidity score (odds ratio [OR]: 1.289, P = .002), the presence of cardiovascular (OR: 2.584, P = .016) and endocrine (OR: 4.234, P = .001) disorders, a 2-stage surgery (OR (ref = 1-stage): 6.506, P = .0003) and a greater number of decompressed levels (OR: 1.816, P = .002). Based on multivariate analysis, patients were at an increased risk of perioperative dysphagia if they had diabetes mellitus (OR (ref = absence): 3.686, P = .001), a greater number of decompressed segments (OR: 1.522, P = .049), and a 2-stage surgery (OR (ref = 1-stage): 3.423, P = .037). Clinical improvements, as evaluated by the Nurick and mJOA, were comparable between patients with and without dysphagia at both short- and long-term follow-up. In contrast, patients with dysphagia had significantly worse scores on the NDI at 6 months postoperatively than patients without dysphagia; however, at 24 months postoperatively, there were no differences between groups. CONCLUSION: The most important predictors of dysphagia are diabetes mellitus, a greater number of decompressed levels, and a 2-stage surgery. Patients with postoperative dysphagia have reduced disability and quality-of-life improvements in the short term but not in the long term.